2010
DOI: 10.1128/aac.00615-09
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Pharmacokinetics, and Safety of Triclosan after Dermal Administration

Abstract: We evaluated the pharmacokinetics and safety of the antimicrobial agent triclosan after dermal application of a 2% triclosan-containing cream to six volunteers. Percutaneous absorption calculated from urinary excretion was 5.9% ؎ 2.1% of the dose (mean ؎ standard deviation). The amount absorbed suggests that daily application of a standard adult dose would result in a systemic exposure 890 times lower than the relevant no-observed-adverse-effect level. Triclosan can be considered safe for use in hydrophobic cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 19 publications
(23 reference statements)
1
56
0
Order By: Relevance
“…Typical routes of exposure to TCS (oral, dermal) are sufficient in bringing the compound into systemic circulation (38,39). Importantly, one study reported plasma C max of nearly 1 μM within 1-3 h after administering a 4-mg oral dose in human subjects (38).…”
Section: Discussionmentioning
confidence: 99%
“…Typical routes of exposure to TCS (oral, dermal) are sufficient in bringing the compound into systemic circulation (38,39). Importantly, one study reported plasma C max of nearly 1 μM within 1-3 h after administering a 4-mg oral dose in human subjects (38).…”
Section: Discussionmentioning
confidence: 99%
“…When men applied cream containing 2% TCS on their skin in a clinical study, the absorption of TCS, calculated from urinary excretion, was estimated to be less than 10% in all individuals (42). A similar study by Lin (43) determined that the TCS retention rate was 7.33% from mouthwash containing 0.03% TCS.…”
Section: Tcs Metabolism and Human Exposurementioning
confidence: 99%
“…However, despite the almost ubiquitous occurrence of triclosan, pharmacokinetic studies on this compound are sparse [31]. In a previous study of orally ingested triclosan in humans, the drug appears to be readily absorbed from the gastrointestinal tract and has a rapid turnover.…”
Section: Discussionmentioning
confidence: 99%